Optimum immobilization of β-Glucosidase enzyme in ca-alginate and acid functionalized-multiwalled carbon nanotubes and comparison of the catalyst effectiveness - Maalim, Kauthar Yusuf; Jameel, Ahmed Tariq; Yusof, Faridah (Kulliyyah of Engineering International Islamic University Malaysia P.O. Box 10, 50728 Kuala Lumpur, Malaysia, 2016)
The optimum conditions for immobilization of β-Glucosidase on multiwalled carbon nanotubes (MWCNTs) and Ca-alginate beads were studied. The effectiveness of the reaction of the immobilized enzyme with pnitrophenyl-β-D-glucopyranoside as substrate is evaluated. For the same substrate concentration the activity of enzyme immobilized in Ca-alginate beads was lower than that of immobilization on MWCNTs. The optimum immobilization conditions were found to be 17 mg MWCNT and 4 hr incubation time for MWCNTs while for calcium-alginate gel, it was found to be 3.5 wt% Na-alginate and 2 hr incubation time. The immobilization yield of the enzyme on MWCNTs was found to be 63.91% and that of Ca-alginate beads was 53.56%. Upon subsequent use, the residual activity of the enzyme on MWCNTs was higher than that of the Ca-alginate beads, which lost almost 50% of the activity at the third run. Both Ca-alginate and MWCNT immobilized enzyme were found to follow Michaelis-Menten kinetics and were well represented by Langmuir plot which was finally used to determine Michaelis-Menten constants. The values of Vmax and Km for MWCNTs are 4.7 μmol/mL.min and 0.833 mM respectively while for Ca-alginate the constants are 4.428 μmol/mL.min and 0.2587 mM respectively.